Nilai-Nilai Moral Islam dan Keseteraan Gender dalam Novel Eliana Karya Tere Liye - Ida Novianti; Wahyu Budiantoro (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
Eliana's novel emphasizes Islamic moral values and gender equality, where these values are inserted through dialogues and activities carried out by the characters. Starting from the first chapter, Eliana has been depicted as a girl who has an awareness that society treats boys and girls differently solely based on their sex. So she tried to show that her abilities were commensurate with boys deserving of awards. This characteristic is considered strange and unusual for the society in the village. The moral values of Islam contained in Eliana's novels include tauhid, honesty, courage, cooperation, qana'ah, discipline, love, birrul walidain, responsibility, keeping promises, harmony, love of nature, forgiveness and earnest . The value of gender equality in Eliana's novel is seen from three things, namely the views of male and female figures and vice versa, the image of male and female leaders, and the roles of male and female leaders.